Probiotics in the next-generation sequencing era. (2nd January 2020) - Suez, Jotham; Zmora, Niv; Elinav, Eran
ABSTRACT: Technological developments, including massively parallel DNA sequencing, gnotobiotics, metabolomics, RNA sequencing and culturomics, have markedly propelled the field of microbiome research in recent years. These methodologies can be harnessed to improve our in-depth mechanistic understanding of basic concepts related to consumption of probiotics, including their rules of engagement with the indigenous microbiome and impacts on the human host. We have recently demonstrated that even during probiotic supplementation, resident gut bacteria in a subset of individuals resist the mucosal presence of probiotic strains, limiting their modulatory effect on the microbiome and on the host gut transcriptional landscape. Resistance is partly alleviated by antibiotics treatment, which enables probiotics to interact with the host at the gut mucosal interface, although rather than promoting reconstitution of the indigenous microbiome and of the host transcriptional profile, they inhibit these components from returning to their naïve pre-antibiotic configurations. In this commentary, we discuss our findings in the context of previous and recent works, and suggest that incorporating the state-of-the-art methods currently utilized in microbiome research into the field of probiotics may lead to improved understanding of their mechanisms of activity, as well as their efficacy and long-term safety.